Evaluasi sikap siswa terhadap perpustakaan sekolah - Hanna Herfina; Hanny Hafiar (Jurnal Kajian Informasi dan Perpustakaan, 2017)
The school library is not yet a favorite place for elementary school students. Many  factors have contributed to this, among other the types of books available, unreliable library time, non-permanent librarians, even the scorn of friends who think of reading in the library as behavior that pretending to diligent. Many factors have contributed to this, such as the types of books available, unreliable library time, non-permanent librarians, even the scorn of friends who think of reading in the library as pretending to be diligent and smart, which cause students to be reluctant to regularly visit the library. Hence, classroom teachers need to reaffirm the library functions and persuade students to visit and utilize facilities in the library. This article presents the evaluation results of students attitude after receiving information about the library described by the classroom teacher. The method used in this study was descriptive study, with fourth-grade students of an elementary primary school as the object, data collection techniques used questionnaires, and data analysis used a single tabulation based on quantitative data. The results showed that students had a better attitude toward school libraries, from the cognitive aspects were such as knowledge, trust, and assessment, and the affective as well as conative aspects. Therefore, it is expected that schools through the classroom teacher can intensively spread information about the function of school libraries, and improve library facilities and services to the students, so they are accustomed to using the library as a first step in forming the love-literacy generation.